Identification of factors associated with the efficacy of atomoxetine in adult attention‐deficit/hyperactivity disorder. Issue 3 (29th April 2022) - Nagai, Tsutomu; Kurihara, Tatsuya; Koya, Hiroaki; Nakano, Yukako; Sugisawa, Satoru; Sambe, Takehiko; Kishimoto, Keiko; Kogo, Mari; Ota, Haruhisa; Iwanami, Akira; Uchida, Naoki
Abstract: Aim: Atomoxetine (ATX) is a non‐central stimulant and a standard treatment for adult attention‐deficit/hyperactivity disorder (ADHD). The long‐term efficacy of Atomoxetine is about 40% at 6 months. The variability in efficacy between individuals is thought to be related to patient‐specific factors, but no detailed research has been conducted. In this retrospective cohort study, we aimed to identify the factors associated with Atomoxetine efficacy. Methods: A total of 147 patients with attention‐deficit/hyperactivity disorder aged ≥18 years who were using Atomoxetine for the first time were included in this study. The outcome was treatment success (treatment maintained for at least 6 months and improvement in symptoms). Symptom assessment was based on the overall improvement in symptoms judged by an expert physician. Results: Of the patient sample, 103 (70.1%) achieved the outcome. Logistic regression analysis identified "the maximum dose of ATX" and "gambling habit" as factors associated with efficacy ( P < 0.05). In the process of Atomoxetine titration, the larger the maximum dose, the higher the efficacy was shown to be. Gambling habits may be indicative of impulsivity, which is among the core symptoms of attention‐deficit/hyperactivity disorder. Thus, a gambling habit may be considered a surrogate marker for impulsivity. Conclusions: Knowledge of these factors will help healthcare professionals to predict the likely efficacy of Atomoxetine in a given patient before subscribing it, facilitating individualized pharmacotherapy for adult attention‐deficit/hyperactivity disorder. Abstract : We retrospectively examined factors associated with the efficacy of atomoxetine for adult ADHD. The maximum dose of atomoxetine and gambling habit were identified as significant factors related to the efficacy.